PEO composite solid polymer electrolytes with the synergistic effect of cryogenic engineering and trace BP nanosheets for nearly room temperature and 4 V class all-solid-state lithium batteries. Issue 3 (18th January 2023) - Tan, Jiewen; Wang, Zhen; Cui, Jiawu; Chen, Yuhua; Jia, Zhanhui; Yang, Mingyu; Gemingjiang, Naziyila; Xiao, Zichun; Wang, Xiaowei; Gao, Wangjiang; Tian, Wensheng; Zhang, Chao; et al.
Abstract : A novel PEO-based SPE with a synergistic effect of black phosphorus (BP) nanosheets and a cryogenic method, which can combine the advantages of the fast Li + pathways of BP nanosheets and the low PEO crystallization of cryogenic method. Abstract : Poly(ethylene oxide) (PEO)-based solid polymer electrolytes (SPEs) are considered promising candidates for next-generation high-safety lithium batteries, however, long-termly limited by their inferior ionic conductivity, low lithium ionic transference number, and insufficient electrochemical stability, especially at room temperature. Herein, we report a novel PEO-based SPE with the synergistic effect of black phosphorus (BP) nanosheets and a cryogenic method, which combined the advantages of the fast Li + pathways of BP nanosheets and low PEO crystallization induced by the cryogenic process. The addition of BP nanosheets could promote the dissociation of LiTFSI and provide long-range Li + -migration pathways in the BP/PEO interface. The cryogenic strategy could reduce the sizes of the PEO crystals apart from the BP/PEO interface and further improve the ionic conductivity and Li + -transference number of the composite SPEs. As a result, the cryogenic PEO-based SPEs with only 0.05% wt BP nanosheets (C-BP SPEs) displayed an excellent ionic conductivity of 3.38 × 10 −5 S cm −1, which was 15.7 times higher than that of pristine PEO SPEs, and a wide electrochemical stability at 30 °C. NCM622/SPEs/Li cells with C-BP SPEs could provide a high discharge capacity of 150.2 mA h g −1 at 0.1C as well as satisfactory cycling performance with a capacity retention of 88.1% after 500 cycles at 0.5C at 30 °C. Importantly, pouch cells were assembled to demonstrate the suitability of the C-BP SPEs for practical application and displayed good electrochemical performance.